Catalytic reduction of nitrophenol and MB waste water using homogeneous Pt NPs confined in hierarchically porous silica. Issue 4 (August 2021) - Subhan, Fazle; Aslam, Sobia; Yan, Zifeng; Yaseen, Muhammad; Marwat, Anum; Ahmad, Ayaz
Abstract: Pt-containing catalysts are considered promising for diverse catalytic reactions, and their activity strongly depends on the dispersion degree of Pt nanoparticles (Pt NPs). In this study, we report an ultrasound assisted impregnation (UAI) strategy to promote Pt NPs dispersion in the nanoconfined spaces of as-prepared ZSM-5 derived micro-/mesoporous silica (MMZ) occluded with template. The precursor of Pt is successfully inserted into the nanoconfined spaces inherent in as-prepared MMZ (between the silica walls and cetyltrimethylammonium bromide (CTAB) template). The Pt NPs formed in the confined spaces were of smaller size than those generated through traditional ZSM-5 without confined spaces. Further calculations based on transmission electron microscopy (TEM) images indicates that the size of 1 wt% Pt per gram of MMZ (denoted as 1 wt%Pt/MMZ) is 3.8 nm, which is lower than that in 1 wt%Pt/ZSM-5. Experimental results demonstrated that well dispersive Pt NPs in 1 wt%Pt/MMZ catalyst led to the complete reduction of para nitrophenol (P-NP) and methylene blue (MB) with reaction rate constant (K) of 0.321 and 0.512 min −1, respectively, which are obviously higher than those of 1 wt%Pt/ZSM-5 and other reported Pt-based catalysts. 1 wt%Pt/MMZ catalyst exhibited good stability and recyclability than 1 wt%Pt/ZSM-5, and hence can be deemed of potential value for practical applications of wastewater treatment on industrial level. Graphical Abstract: ga1 Highlights: Ultrasound assisted impregnation (UAI) strategy regulates high dispersion of Pt NPs over MMZ. MMZ favors the formation of smaller size Pt NPs compared with ZSM-5. 2-D nanoconfined spaces of MMZ strongly avoided aggregation of Pt NPs. CTAB and silanols of MMZ establish strong interaction of Pt NPs with MMZ. Highly dispersed Pt NPs are effective for reduction of P-NP to P-AP and MB to LMB.